KEDUDUKAN CESSIE SEBAGAI OBJEK JAMINAN BERDASARKAN HUKUM JAMINAN DI INDONESIA - fazur, Muhammad Fazur Rohman Trisno; Wahyoeono H, Dipo (Journal Evidence Of Law, 2023)
This research examines the role of cessie as a collateral object in the context of security law in Indonesia. Cessie is a common form of collateral used in business transactions in Indonesia, involving the transfer of rights or interests from a debtor to a creditor. The aim of this research is to understand the concept and basic understanding of cessie and collateral in Indonesian security law, as well as to analyze the position of cessie as a collateral object in the legislation governing security law in Indonesia. The research method used is normative legal research, involving the analysis of legislation, court decisions, and relevant legal literature. The results of this research show that cessie is a transfer of receivables governed by the Indonesian Civil Code (BW). Cessie can be understood as a legal institution of obligations, involving the substitution of creditors, and as part of property law, involving the transfer of ownership rights. Cessie is considered a valid collateral object if it meets the requirements stipulated in the legislation. This research also identifies several issues related to the position of cessie as a collateral object, such as legal clarity regarding the registration mechanism and the enforcement of rights over cessie, as well as legal protection that aligns with principles of justice and balance. This research provides recommendations to enhance legal protection for cessie as a collateral object, in accordance with the development of the legal system in Indonesia. With a better understanding of the position of cessie as a collateral object, it is hoped that an effective and efficient collateral system can be developed, creating a conducive investment climate in Indonesia. This research contributes to the field of security law and can serve as a guide for policymakers in improving legal protection for cessie as a collateral object.